SUSTAINABILITY INDICATORS FOR MUNICIPALITIES IN THE ABC PAULISTA REGION: ARE THEY MEETING THE SUSTAINABLE DEVELOPMENT GOALS? (Gestão & Regionalidade, 2025)
This article presents a study on the Sustainable Development Goals (SDGs), the fulfillment of the Goals of the 2030 Agenda of the United Nations (UN) and how they are being fulfilled in the seven municipalities of the ABC Paulista Region. The aim was to compare the situation of the municipalities using two sustainability indicators: the Sustainable Development Index for Cities - Brazil (IDSC-BR) and the Sustainable Development Goals - Brazil (SDG-BR). The methodology involves collecting secondary data on the IDSC-BR and SDG-BR sustainability indicators from the seven cities that make up this region. The analysis compares the situation of each municipality in relation to each SDG and in relation to the other municipalities in the region. The results show that, regardless of the origin of the matrices, there is an alignment between the municipalities in terms of progress in relation to the SDGs, environmental demands, factors, attributes and performance indicators of the SDGs of the seven cities.